Presymptomatic atrophy in autosomal dominant Alzheimer's disease: A serial magnetic resonance imaging study. Issue 1 (21st July 2017) - Kinnunen, Kirsi M.; Cash, David M.; Poole, Teresa; Frost, Chris; Benzinger, Tammie L.S.; Ahsan, R. Laila; Leung, Kelvin K.; Cardoso, M. Jorge; Modat, Marc; Malone, Ian B.; Morris, John C.; Bateman, Randall J.; et al.
Abstract: Introduction: Identifying at what point atrophy rates first change in Alzheimer's disease is important for informing design of presymptomatic trials. Methods: Serial T1‐weighted magnetic resonance imaging scans of 94 participants (28 noncarriers, 66 carriers) from the Dominantly Inherited Alzheimer Network were used to measure brain, ventricular, and hippocampal atrophy rates. For each structure, nonlinear mixed‐effects models estimated the change‐points when atrophy rates deviate from normal and the rates of change before and after this point. Results: Atrophy increased after the change‐point, which occurred 1–1.5 years (assuming a single step change in atrophy rate) or 3–8 years (assuming gradual acceleration of atrophy) before expected symptom onset. At expected symptom onset, estimated atrophy rates were at least 3.6 times than those before the change‐point. Discussion: Atrophy rates are pathologically increased up to seven years before "expected onset". During this period, atrophy rates may be useful for inclusion and tracking of disease progression.